Systenotelus, a remarkable new genus of weevil (Coleoptera: Curculionidae) associated witb Carludovica (Cyclantbaceae) in Costa Rica and Panamá - Anderson, Robert S (Universidad de Costa Rica, 1997)
Systenotelus Anderson & Gómez, new genus, is described with three included species, S. carludovicae Anderson & Gómez, new species (Costa Rica), S. costaricensis Anderson & Gómez, new species (Costa Rica and Panama), and S. stockwelli Anderson & Gómez, new species (Panama). Adults of Systenotelus are distinguished by very elongate-narrow genitalia in females, female pygydium constricted near the midlength, and tumescent mesostemal process. They are relatively large in body size (4.9-12.4 mm), are pale to dad: yellow in color and possess various black dorsal and lateral maculations. Adults are remarkable in that the apex oC the abdomen is moderately to markedly tapered in females and the genitalia and associated structures of both sexes are modified and very elongate-narrow. Adults of S. carludovicae have been collected on freshly opened inflorescences of Carludovica palmata Ruíz & Pavón and C. drudei Masters (Cyclanthaceae) in Costa Rica; adults of S. costaricensis have been collected on inflorescences of Carludovica drudei in Panama; and, adults of S. stockwelli have been collected on inflorescences of Carludovica palmata in Panama. Systenotelus is a member of the tribe Derelomini of the Curculioninae (sensu Kuschel), many other species of which attend flowers of various Cyclanthaceae and Arecaceae. The closest relative of Systenotelus appears to be an undescribed monotypic genus associated with Sphaeradenia hamata Harl.(Cyclanthaceae) in Colombia.